Assessment of Young Drivers' Driving Behaviour and Driving Speed Along Horizontal and Vertical Alignments - Mior Ahmad Termidi, Wan Nur Sakinah; Mashros, Nordiana; Hassan, Sitti Asmah; Faiz, Rizwan Ullah; Mohamed, Azman; Abd Rahman, Raha (International Journal of Integrated Engineering, 2021)
Young drivers are more likely to experience car crashes as they tend to have risky driving behaviours. This study aims to assess young drivers' driving behaviour and driving speed along the horizontal and vertical alignments of roads. The 20 young drivers who participated in this study were asked to complete a self-reported assessment (Driver Behaviour Questionnaire) and then invited for an on-road driving assessment during daytime and night-time, along horizontal and vertical road alignments at a selected route in Skudai, Johor. The results from the Driver Behaviour Questionnaire revealed that distractions during driving was the most frequently reported behaviour that caused car crashes amongst young drivers, followed by error and violation. Speed profile was found to be higher during daytime when compared to night-time. A significant difference in speed between male and female drivers was noted at horizontal curves during daytime and vertical curves during night-time. The study concluded that such aberrant driving behaviours would have an impact on the driving performance, particularly on horizontal and vertical curves.